Adoption of Sandy Coastal Farming Technology in Indonesia: A Household Economics Analysis - Fauzan, Muhammad; Syaukat, Yusman; Kusnadi, Nunung; Baga, Lukman Mohammad (Universitas Muhammadiyah Yogyakarta, 2025)
Sandy coastal farming has become a crucial livelihood strategy in Indonesia's marginal coastal areas, yet technology adoption remains uneven across farmer households. This study examines how the economic behavior of farmer households influences the intensity of sandy coastal farming technology adoption and analyzes how changes in internal and external factors impact adoption, production, labor allocation, income, and expenditure. Using primary cross-sectional data from 196 farmer households in Bantul Regency, Yogyakarta, the study applies an integrated household economic model estimated as a system of simultaneous equations using the Two-Stage Least Squares method. Technology adoption is represented through the allocation of cultivated land and the use of soil-improving inputs, allowing for the examination of adoption intensity within a unified household decision framework. The results show that adoption intensity is primarily driven by household income and family labor availability, with cultivated area acting as a key transmission channel linking income to input use and production outcomes. Higher returns from sandy coastal farming induce substitution toward hired labor rather than proportional increases in family labor. Simulation results indicate that output price incentives strengthen adoption through income and scale effects, while reductions in irrigated land weaken adoption by tightening household resource constraints. These findings underscore the significance of income stability and access to resources in maintaining high adoption intensity in marginal land systems.